Asymptomatic Carriage of Listeria monocytogenes by Animals and Humans and Its Impact on the Food Chain - Dagmar Schoder; Claudia Guldimann; Erwin Märtlbauer (Foods, 2022)
Humans and animals can become asymptomatic carriers of Listeria monocytogenes and introduce the pathogen into their environment with their feces. In turn, this environmental contamination can become the source of food- and feed-borne illnesses in humans and animals, with the food production chain representing a continuum between the farm environment and human populations that are susceptible to listeriosis. Here, we update a review from 2012 and summarize the current knowledge on the asymptomatic carrier statuses in humans and animals. The data on fecal shedding by species with an impact on the food chain are summarized, and the ways by which asymptomatic carriers contribute to the risk of listeriosis in humans and animals are reviewed.